Visual over auditory superiority in sensorimotor timing under optimized condition - Zhan, Liying; Huang, Yingyu; Guo, Zhihan; Yang, Junkai; Gu, Li; Zhong, Shengqi; Wu, Xiang (Frontiers in Psychology, 2022)
Auditory over visual advantage in temporal processing is generally appreciated, such as the well-established auditory superiority in sensorimotor timing. To test for a possible visual superiority in temporal processing, here, we present a data set composed of a large sixty-subject sample and a data set including eight smaller samples of approximately fifteen subjects, showing that synchronization to a temporally regular sequence was more stable for a visual bouncing ball than for auditory tones. The results demonstrate that vision can be superior over audition in sensorimotor timing under optimized conditions, challenging the generally believed auditory superiority in temporal processing. In contrast to the auditory-specific biological substrates of timing in sensorimotor interaction, the present finding points to tight visual-motor cortical coupling in sensorimotor timing.